Desmoplastic melanoma: a review of its pathology and clinical behaviour, and of management recommendations in published guidelines. (3rd March 2021) - Hughes, T.M.; Williams, G.J.; Gyorki, D.E.; Kelly, J.W.; Stretch, J.R.; Varey, A.H.R.; Hong, A.M.; Scolyer, R.A.; Thompson, J.F.
Abstract: Desmoplastic melanomas are uncommon. Their behaviour differs from that of other melanoma subtypes; therefore, management guidelines for non‐desmoplastic melanomas may not be applicable. This review sought to examine all available evidence relating to the behaviour and management of desmoplastic melanomas, based on review of all relevant English‐language publications, and to critically assess the recommendations for their management in current published melanoma management guidelines. Compared with other melanoma subtypes, patients with 'pure' desmoplastic melanomas (where ≥90% of the invasive melanoma is of desmoplastic melanoma subtype) have much lower rates of sentinel node positivity and distant metastasis. Local recurrence rates are higher for desmoplastic melanomas, but resection margins wider than those recommended for non‐desmoplastic melanomas have not been shown to be of benefit. Adjuvant radiotherapy reduces the risk of local recurrence when a satisfactory histological clearance (≥8 mm) cannot be achieved. Of 29 published melanoma management guidelines identified, only 11 specified management for desmoplastic melanomas, while seven simply stated that the feature should be reported. Desmoplastic melanoma is a unique melanoma subtype with biology that differs from that of other melanoma subtypes. It requires specific management strategies but few current guidelines address these.